Open Water Jumping: Clearing Obstacles in the Negotiation of French Rights to The Black Stallion - Cécile Cottenet (Transatlantica)
Walter Farley’s stallion, Black, is certainly remembered as one of the most famous and beloved animals in Hachette’s Bibliothèque verte. The numerous titles in the “Black Stallion” series were reedited several times, and ultimately achieved high sales. The story of the introduction of the series in France in the aftermath of World War II, and its inclusion in this now-classic library of children’s texts, is largely unknown. Behind the scenes of the transatlantic negotiations, a narrative of complex, arduous discussions between author, series editor and agents unfolds, revealing the roles played by mediators usually forgotten by literary history. Based on archival evidence, this article develops a book history perspective to shed some light on these long negotiations that took place between 1941 and 1964.